2002
DOI: 10.1034/j.1600-0447.2002.02270.x
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal behaviour of psychiatric in‐patients

Abstract: As Schizophrenics represent the high-risk group of in-patient suicide, suicide prevention should be a major goal in their treatment. More frequent suicide risk assessment is recommended particularly before granting a leave or an outing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
15

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 27 publications
3
29
0
15
Order By: Relevance
“…A reanalysis of studies of suicide in affective illness in three groups of patients-outpatients, inpatients, and suicidal patients-found a risk of those ever hospitalized of 8.6% (3). Other studies confirmed the risk of suicide to be particularly high in hospitalized depressed patients (4)(5)(6). Profound hopelessness, hypochondriacal ruminations or delusions, and thoughts of suicide or self-harm during depression predict future suicide (7).…”
mentioning
confidence: 99%
“…A reanalysis of studies of suicide in affective illness in three groups of patients-outpatients, inpatients, and suicidal patients-found a risk of those ever hospitalized of 8.6% (3). Other studies confirmed the risk of suicide to be particularly high in hospitalized depressed patients (4)(5)(6). Profound hopelessness, hypochondriacal ruminations or delusions, and thoughts of suicide or self-harm during depression predict future suicide (7).…”
mentioning
confidence: 99%
“…These include socio-demographic factors such as age (Christiansen and Jensen, 2007;Corcoran et al, 2004), unemployment (Tejedor et al, 1999), not being married (Kreitman and Foster, 1991) or low educational level (Christiansen and Jensen, 2007) which have been associated with repetition of suicidal behaviour (Osvath et al, 2003). Clinical factors include lethality of the index attempt (Gibb et al, 2005), poor physical health (Colman et al, 2004), and mental illness or psychiatric comorbidity, which has been noted to be a risk factor for repetition in studies on parasuicides (Colman et al, 2004;Osvath et al, 2003), non-fatal suicidal behaviours (Kapur et al, 2006) and SAs among inpatients (Spiessl et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Schizophrenia, in particular, is associated with a higher risk of suicide than in the general population [9], with men being at higher risk than women [10][11][12][13][14][15]. Furthermore, it seems that, in schizophrenic patients, active illness, depressive symptoms, alcoholism and a history of previous suicide attempts and/or suicidal ideation are highly prevalent immediately before suicide [10,[14][15][16].…”
Section: Discussionmentioning
confidence: 99%